Molecular Insights and Management Strategies for Rare Inherited Metabolic Disorders Presenting with Neurological Symptoms in Pakistan - Muzammal, M.; Shafiq, M.; Khan, A. S.; Istiaq , S.; Siddiqua , A.; Malik , H.; Batool, S.; Hussain, M.; Said, A.; Hassan, K. N.; Rustam, S. A.; Hashmi, H. B.; et al. (The Nucleus, 2026)
Inborn errors of metabolism (IEM) are disorders caused by defects in a biochemical pathway that relate to the metabolism of a metabolite due to the action of a single gene. IEM creates a block to the normal synthesis as well as degradation of compounds during metabolism. Metabolism can be thought of as a complex and chaotic assembly line of chemical reactions, yielding both good and waste products. Raw materials, partially finished products, and waste products are present that are being supplied, synthesized, transported, and excreted continuously. The "workers" on the assembly line are enzymes and proteins that are utilized to chemically convert reactants into forms that are useful or to generate waste. So far, more than 60 IEMs have been reported worldwide, but only few have been identified in Pakistan. This may be due to unawareness and poor condition of the families suffering from these disorders. Here in the current review, we tried to highlight some of the rare metabolic disorders causing variable phenotypes, including Intellectual disability (ID), speech defect, kidney and heart issues, and bone and muscle issues as well. This review will discuss recent genetic etiological advances in inherited metabolic disorders and summarize epidemiological data and clinical diagnostic challenges, focusing on inherited metabolic disorders (IMDs) in the Pakistani population.